Time Accessibility Pattern Changes in Response to New Fast Transportation Mode: Approaches and Applications - Hong, Wuyang (2018 26th International Conference on Geoinformatics, 2018)
In recent years, the development of a high-speed railway has become an important influencing factor in the process of regional pattern changes in China. Strengthening traffic accessibility has the most direct impact on regional development. As a case study, Nanjing, an urban agglomeration transportation hub of the high-speed railway in South Jiangsu, was selected as the object of this research. In this study, we conducted the cumulative cost distance algorithm in geographic information system (GIS) to construct the accessibility evaluation model based on minimum distance partition, which helps to analyze the effect on the accessibility pattern of regional central cities in urban agglomerations scale. The results indicated that the high-speed railways increased regional space-time contraction and reduced the time cost between areas to improve the overall level of regional accessibility. Time costs of each node to Nanjing diminished slightly, and the accessibility gap narrowed gradually. More cities achieve cross-city day flow and result in Urban Integration effect which can be profound influence on the economic and spatial structure. Furthermore, HSR services are intended to be medium-and long-distance connections as the isochronous rings of 90 min and 120 min significantly expanded the scope. Also, the improvement of accessibility by high-speed railway has the Hourglass Effect according to city scale.